Overt Subjects And Agreement In Zulu Infinitives - Halpert, Claire (My University, 2022)
This paper explores a surprising interaction of agreement and concord inside infinitive clauses in Zulu. In Zulu, as in many Bantu languages, infinitive verbs are marked with noun class 15/17 morphology. Internal arguments of infinitives are typically unmarked, while the external argument must receive so-called associative morphology and must precede internal arguments. I argue that the external argument in these constructions is realized in Spec,vP, a finding that has a number of consequences for our understanding of clause structure and agreement in Zulu and related languages.
Keywords: zulu; infinitive clauses; bantu language